2014
DOI: 10.7567/apex.7.082101
|View full text |Cite
|
Sign up to set email alerts
|

Electrically pumped room-temperature operation of GaAs1−xBixlaser diodes with low-temperature dependence of oscillation wavelength

Abstract: Lasing oscillation at wavelengths up to 1045 nm at room temperature has been realized from GaAs1−xBix Fabry–Perot laser diodes (FP-LDs) by electrical injection, and the temperature characteristics of GaAs1−xBix FP-LDs are revealed for the first time. The characteristic temperature T0 of the GaAs0.97Bi0.03 FP-LD in the temperature range between 15 and 40 °C (T0 = 125 K) is similar to that reported for typical 0.98 µm InGaAs/GaAs LDs. The temperature coefficient of the lasing wavelength in GaAs0.97Bi0.03 FP-LDs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 21 publications
(29 reference statements)
6
26
0
Order By: Relevance
“…Electrically pumped lasing at RT is demonstrated under pulsed excitation with a threshold current density of 1.56 kA/cm 2 for a 1 mm long cavity at an emission wavelength of 947 nm. Later in 2014, Yoshimoto et al reported lasing oscillation up to 1045 nm at RT from electrically pumped GaAs 1−x Bi x FP lasers (x Bi ≤ 4%) [264]. For GaAs 0.97 Bi 0.03 QW lasers, the characteristic temperature in the temperature range of 15-40 • C is 125 K, higher than that in a typical 1.3 µm InGaAsP FP laser.…”
Section: Telecom and Mir Lasersmentioning
confidence: 99%
“…Electrically pumped lasing at RT is demonstrated under pulsed excitation with a threshold current density of 1.56 kA/cm 2 for a 1 mm long cavity at an emission wavelength of 947 nm. Later in 2014, Yoshimoto et al reported lasing oscillation up to 1045 nm at RT from electrically pumped GaAs 1−x Bi x FP lasers (x Bi ≤ 4%) [264]. For GaAs 0.97 Bi 0.03 QW lasers, the characteristic temperature in the temperature range of 15-40 • C is 125 K, higher than that in a typical 1.3 µm InGaAsP FP laser.…”
Section: Telecom and Mir Lasersmentioning
confidence: 99%
“…To date, there have been a few studies on the utilization of the GaAs 1 À x Bi x material system as the solar cell base region material [10], although several demonstrations for light emitting devices have been shown [11][12][13][14]. For the photovoltaic application, when grown on a GaAs substrate, the GaAs 1 À x Bi x material system has Contents lists available at ScienceDirect journal homepage: www.elsevier.com/locate/jcrysgro the advantage over the more conventional In z Ga 1 À z As material system in that a smaller compressive strain is induced at the same band gap energy, allowing a much thicker GaAs 1 À x Bi x to be employed without encountering strain relaxation; thus leading to increased optical absorption from a thicker solar cell base region.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a GaAsBi film with 2.6% Bi has a temperature coefficient of the band gap only 1/3 of that of GaAs near room temperature. 4 This property can lead to the realization of temperature-insensitive devices, 5 as confirmed in a study of GaAsBi-based laser diodes, 6 and benefits a number of technologies. Third, Bi atoms strongly increase the spin-orbit splitting of GaAsBi, and for Bi contents near 10%, it is expected to totally suspend one type of Auger recombination, 3,5 which induces the serious 'efficiency droop' in high-energy light-emitting diodes and laser diodes.…”
Section: Introductionmentioning
confidence: 99%
“…13 These defect-related issues have become a bottleneck in the successful applications of GaAsBi. For instance, to date, GaAsBi-based laser diodes require a threshold current density (2-10 kA cm − 2 ) 6,[14][15][16] that is approximately an order of magnitude higher than that of typical InGaAs-based laser diodes (0.2-0.5 kA cm − 2 ).…”
Section: Introductionmentioning
confidence: 99%